Analisis Permasalahan Guru dan Siswa Menggunakan Pembelajaran Berbasis Masalah dengan Media LCD (Liquid Crystal Display) Terhadap Hasil Belajar IPA Biologi - Faridah Faridah; Elsje Theodora Maasawet; Didimus Tanah Boleng (Fakultas Sains dan Teknologi, UIN Walisongo Semarang, 2018)
The function of education is to prepare students through a process that takes place before students are ready to work in real life. The strategy for implementing education is carried out in the form of guidance, teaching and training activities. In line with that national education must be able to guarantee equal opportunities for education, improvement in quality, and efficiency of education management. Improving the quality of education is directed at improving the quality of Indonesian people as a whole through cognitive, affective aspects, and psychomotor aspects. The purpose of the study was to determine the problems of teachers and students in the problem-based learning model with the use of Liquid Crystal Display Media on the results of Biology Science. The design of this study uses quasi experimental. Based on observations and interviews with Biology Science teachers that students tend to remain silent in class, pay less attention to teachers, play with their peers so that the average cognitive learning value results are 63.50%. Based on the results of interviews with students, information was obtained that the teacher had been giving a woman a monotonous method, namely lecture and lack of interaction with students so that some students felt they did not understand the material.